1989
DOI: 10.1002/ijc.2910430207
|View full text |Cite
|
Sign up to set email alerts
|

An anti‐CD5 immunotoxin for chronic lymphocytic leukemia: Enhancement of cytotoxicity with human serum albumin‐monensin

Abstract: Five patients with B-cell chronic lymphocytic leukemia (B-CLL) were treated with 6 courses of the anti-CD5 immunotoxin T101-ricin A chain (T101-RTA). Each course consisted of 8 bi-weekly infusions of T101-RTA (7 or 14 mg/m2). The immunotoxin was well tolerated in all cases with no major toxicities. Though saturation of circulating leukemic cell-associated target antigen was demonstrated by FACS analysis in all patients, no intact immunotoxin was detected in bone-marrow or lymph-node aspirates. Pharmacokinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…34,35 However, a number of our patient samples were relatively resistant to DTLIL3 suggesting that expression of the IL-3R on leukemic progenitors is variable. It is interesting to hypothesize that the sensitivity of some patient samples to the toxin may reflect the presence of an IL3-IL3R autocrine loop in these cells as has been previously described.…”
Section: Discussionmentioning
confidence: 93%
“…34,35 However, a number of our patient samples were relatively resistant to DTLIL3 suggesting that expression of the IL-3R on leukemic progenitors is variable. It is interesting to hypothesize that the sensitivity of some patient samples to the toxin may reflect the presence of an IL3-IL3R autocrine loop in these cells as has been previously described.…”
Section: Discussionmentioning
confidence: 93%
“…In another phase I trial, T101-RTA was administered in the presence of monensin, covalently linked to human serum albumin (HAS) for cytotoxicity enhancement. In this trial, conducted on 5 B-cell chronic lymphocytic leukemia (B-CLL) patients, no long term clinical effect was observed [126]. These trials were reported in 1989 and no further clinical trials were pursued.…”
Section: T101-rtamentioning
confidence: 95%
“…Some of the antigens targeted in the present study, such as CD5 (Hertler et al, 1989), CD19 (Grossbard & Fidias, 1995) and CD22 (Shan & Press, 1995) have been used as targets for immunotoxins for B-cell malignancies.…”
Section: The Differential Internalization Of Mabs By B-cll Cells In Vmentioning
confidence: 99%